Integrating genetic diversity and biochemical profiling for biofuel-efficient maize genotypes - Pratikshya, Mishra; Abinash, Mishra; Kartik, Chandra Pradhan; Mihir, Ranjan Mohanty; Kailash, Chandra Samal; Manasi, Dash; Dayanidhi, Mishra; Mahendra Kumar, Mohanty; Devraj, Lenka; Digbijaya, Swain (Plant Science Today, 2025)
This study explores the genetic diversity, biochemical composition and trait associations in maize (Zea mays L.) to assess its potential as a dual-purpose crop for food and biofuel production. Significant variations in lignocellulosic traits among the evaluated genotypes indicate opportunities for enhancing bioethanol yields. A comparative biochemical study reveals the cellulose content in the kernel is 2.15 times higher than in stover, whereas the hemicellulose and lignin content in stover are 4.6 times and 5.3 times higher, respectively, compared to the kernel. The inbred lines DQL 2159, DQL 222-1-1 and DQL 2272 exhibited significantly higher cellulose contents of 37.05 %, 35.98 % and 35.53 %, respectively, along with significantly lower lignin contents of 20.65 %, 22.25 % and 22.53 % in maize stover. Correlation analysis shows that shoot dry weight (rp = 0.29), stalk diameter (rp = 0.33) and plant height (rp = 0.48) are positively associated with biomass yield. Biochemical studies reveal a strong negative correlation (rp = -0.59) between kernel lignin and kernel cellulose content, indicating that higher cellulose leads to lower lignin. This finding is valuable for selecting high-cellulose, low-lignin genotypes. Path coefficient analysis further identifies plant height, number of leaves per plant, stalk diameter and kernel cellulose content as key contributors to grain yield, suggesting that selection for these traits could enhance biofuel production. Identifying desirable traits that enhance biofuel efficiency, such as high cellulose and low lignin content, enables targeted breeding for improved biomass conversion. Cluster analysis revealed that Cluster III exhibited superior performance across the majority of traits evaluated, making it the most promising group for utilization in biofuel breeding programs. Notably, genotypes such as DQL 2037, DQL 2272, DQL 2159 and DQL 222-1-1 emerge as promising candidates for biofuel applications due to their high grain and stover yields, alongside elevated cellulose and hemicellulose content. Collectively, these findings provide a comprehensive framework for targeted breeding strategies aimed at developing high-yielding, biofuel-efficient maize cultivars for climate smart agriculture systems.